Performance investigation of adsorption cooling and desalination systems employing thermally enhanced copper foamed bed coated with SAPO-34 and CPO-27(Ni). (25th March 2022) - Shaaban, Mohamed; Elsheniti, Mahmoud Badawy; Rezk, Ahmed; Elhelw, Mohamed; Elsamni, Osama A.
Highlights: CPO-27(Ni) and SAPO-34 coated on foamed adsorption beds are numerically simulated. Comparative studies on the two adsorbents are introduced at a two-bed system level. Adsorption kinetics of SAPO-34 advances its system performance above CPO-27(Ni) Using thicker coated foam enhances the COP of both adsorbent systems noticeably. Abstract: Despite the increasing interest in adsorption cooling and desalination systems, the poor heat hence mass transfer in the adsorbent-bed (the core component) impedes the efficient energy conversion at the system level and increases its physical footprint. In response, this paper numerically investigates the overall enhancement of adsorption cooling cum desalination system employing emerging copper foamed adsorbent beds of advanced thermal performance coated with advanced adsorbent materials to address such an untapped challenge. Silico-aluminophosphate (SAPO-34) and Nickel-based metal-organic framework CPO-27(Ni) adsorbents were employed. First, a 2-D axisymmetric computational fluid dynamic fully coupled model was developed to simulate the adsorbent-beds considering non-ideal condenser and evaporator pressures. Second, the influence of different operating conditions and copper foam thicknesses was investigated at the adsorbent-bed and system levels. The advanced adsorption kinetics of SAPO-34 enabled shortening the cycle time from 600 to 180 s, which enhanced the coefficient of performance (COP), specific cooling power (SCP), and specific daily water production (SDWP) of the system by 163%, 223%, and 228%. The regeneration temperature was the most influential parameter on the systems' performance within the investigated range (70–100 °C). It enhanced the COP from 0.2 to 0.421, SCP from 132 to 821 W.kg −1, and SDWP from 4.7 to 29.3 m 3 .ton -1 .day −1, for CPO-27(Ni) coated bed; and COP from 0.378 to 0.388 and SCP from 393 to 855 W.kg −1 and SDWP from 14 to 31 m 3 .ton -1 .day −1, for SAPO-34 coated bed. The reported enhancements at the adsorption system-level signpost metal-foamed adsorbent-bed coating the most thermally efficient adsorbent-bed design.